Rancang Bangun Game Edukatif Pengenalan Hewan Khas Kalimantan Menggunakan Unity Engine - Dhea Puspita; Muhammad Farman Andrijasa; Bambang Cahyono (JURNAL VOKASI TEKNIK, 2025)
Among children at elementary school level, the introduction of typical Kalimantan animals is still limited, especially at State Elementary School 009 Samarinda Seberang, Mangkupalas Village, East Kalimantan. The learning media at this school still relies on books as the main source. As a solution to this problem, this research aims to create media that can introduce typical Kalimantan animals to children aged 9-12 years, through desktop-based educational games using Unity software with the Game Development Life Cycle (GDLC) method which consists of five stages: Initiation, Pre-production, Production, Testing, and Release. This research was carried out at State Elementary School 009 Samarinda Seberang, Mangkupalas District, East Kalimantan, by carrying out alpha and beta testing, the scenario test results for alpha testing showed 100% results and beta testing with a questionnaire of 50 respondents using a Likert scale for children showed results of 97.1% of children agreeing that this game helps get to know typical Kalimantan animals and for teachers with 11 respondents showing 93% agree that this game helps children get to know 12 typical Kalimantan animals such as the Mahakam Porpoise, Horned Hornbill, Gibbon, Sentarum Langur, Proboscis Monkey, Orangutan, Clouded Leopard, Red Cat, Sun Bear, Capapuya Frog, Pangolin and Pygmy Elephant. The result of this research is an educational game introducing typical Kalimantan animals in desktop-based 3D which has been uploaded via the itch.io platform.